Study on the Perception of the Employees of Some Organizations in Caras-Severin on the Managers’ Characteristics - Solomia Andres (Robotica & Management)
This paper presents the scientific and research methodology together with the interpretation and analysis of data and information obtained through the research applied in 2023, regarding the perception of the employees of some organizations in the Caras-Severin County, Romania, regarding the characteristics of their managers. Based on the reality that a good manager must possess many qualities, knowledge, skills, techniques and methods, in order to identify the elements that define the characteristics of managers, we applied a research based on a questionnaire shared online, consisting of 24 questions, out of which 8 were identification questions and 16 questions were designed to highlight the extent to which organization manager demonstrate the possession of qualities, knowledge, skills, techniques and methods, as well as to highlight the employees’ importance in the development of organizational performance, the importance of communication and trust between employees and managers, the importance of performing managerial functions and more. Analysing the information obtained through the respondents’ answers, we found all proposed objectives were fulfilled, which were mostly positive, even though some less favourable answers were given.